2021
DOI: 10.1002/nme.6680
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic multigrid methods for saddle point systems arising from mortar contact formulations

Abstract: In this article, a fully aggregation-based algebraic multigrid strategy is developed for nonlinear contact problems of saddle point type using a mortar finite element approach. While the idea of extending multigrid methods to saddle point systems can already be found, for example, in the context of Stokes and Oseen equations in literature, the main contributions of this work are (i) the development and open-source implementation of an interface aggregation strategy specifically suited for generating Lagrange m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
(164 reference statements)
0
17
0
Order By: Relevance
“…Since this paper is concerned with the efficient evaluation of the mortar terms on parallel computing clusters, we will detail the discretization of all mortar-related terms in Section 2.2. However, to keep the focus tight and concise, we refer to the extensive literature for any further details on the finite element formulation and discretization [31,48,49,56,57,76,80], the solution of the nonlinear problem via active set strategies [37,43,45,44,55], as well as for details on the structure of the arising linear systems of equations and efficient solvers thereof [2,14,67,69,70,72,71,77].…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this paper is concerned with the efficient evaluation of the mortar terms on parallel computing clusters, we will detail the discretization of all mortar-related terms in Section 2.2. However, to keep the focus tight and concise, we refer to the extensive literature for any further details on the finite element formulation and discretization [31,48,49,56,57,76,80], the solution of the nonlinear problem via active set strategies [37,43,45,44,55], as well as for details on the structure of the arising linear systems of equations and efficient solvers thereof [2,14,67,69,70,72,71,77].…”
Section: Governing Equationsmentioning
confidence: 99%
“…Depending on the specific details of the discretization, the resulting linear system might exhibit saddle-point structure. Efficient preconditioners to be used in conjunction with Krylov solvers are available in literature [2,14,67,69,70,72,71,77] and, thus, are not in the scope of this paper. We rather focus on the cost of evaluating all mortar-related terms.…”
Section: Introductionmentioning
confidence: 99%
“…By using a nonlinear complementarity function, we can merge the search for the active contact set into a semi-smooth Newton method to solve for all nonlinearities within a single iterative scheme. To solve the linear system in each Newton step, we rely on specialized multi-level preconditioners for mortar-based contact formulations [6,7].…”
Section: Governing Equations and Finite Element Discretizationmentioning
confidence: 99%
“…Algebraic multigrid (AMG, [72]) is one of the most effective multilevel approaches and consists of the complementary use of: (i) a smoother that reduces high frequency errors, (ii) a coarse grid correction that reduces low frequency errors, and (iii) restriction and interpolation operators, to move from one grid to another. Starting from the original works, e.g., [73], a wide range of multigrid approaches has appeared in the literature, extending the applicability of this method, originally designed for elliptic PDEs, to both non-symmetric [74,75] and block matrices [76][77][78][79][80][81]. Nonetheless, robustness and efficiency is still an open issue for AMG whenever used as a black-box tool in problems with these algebraic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Jacobian matrix arising from the model considered herein is a non-symmetric 3 × 3 block matrix and, despite the available studies for similar problems, none of them can be straightforwardly and effectively applied to our case. In the context of geomechanical simulations, only a few studies on 2 × 2 block Jacobian systems [80,82,83] are found by the authors.…”
Section: Introductionmentioning
confidence: 99%